Prevalence of dental caries among different stage students in College of Dentistry, Hawler Medical University. - Mahmood Fawzi Abdul‐Jabbar; Blend Hussein Mohammad; Mansour Hadi Mohammad (Erbil Dental Journal, 2022)
Background and Objectives: Dental caries considered as one of the most prevalent diseases affecting teeth. Many organizations are trying to prevent this disease in a variety of ways. The first responsible person professionally for oral health education is the dentist. In order to educate others, one should apply these measures by himself. The aim is to measure the prevalence of dental caries among different stage students, in college of Dentistry/Hawler Medical University. Then relate the prevalence with their academic knowledge of dental caries prevention and to know if males or females have more dental caries, in academically educated dental students about dental caries prevention. Methods: 148 were collected, and the DMFT index scored for them. From which 62 of them were males and 86 females. Peak participation was in the first stage. Females were dominant in participation in all the stages without exception. The female to male ratio was 1.39:1 in the total of all stage participants. Results: The results appeared not significant, with no association between dental caries and academic education of dental caries prevention (p=0.703). There was some difference between the stages, but it was not coincident with having oral health education or not. Conclusion: Academic information has little effect on increasing or decreasing dental caries rates.